PENGARUH LAMA PERENDAMAN TERHADAP AKTIVITAS ANTIOKSIDAN DARI EMPELUR SAGU BARUK (Arenga microcharpha) - Momuat, Lidya Irma; Suryanto, Edi (Sam Ratulangi University, 2016)
Sago baruk is one of endemic crop type of Archipelago of Sangihe Talaud, North Sulawesi. The objectives of this research were to study immersion time effect on antioxidant activity of sago baruk pith extract. The fresh sago baruk trunks pith was extracted with destilate water and stored at room temperature for 1, 2 and 3 days. After that, the filtrate was evaporated with heating technique. The pith extract was analysed phenolic total content by spectrophotometer. Antioxidant activity of each pith extract are evaluated in 1.1-diphenyl-2-picrylhydrazyl (DPPH) radical scavenging (DPPH method), total antioxidant (FRAP method), antioxidant capacity (Phophomolybdate method) and reducing power (potassium ferricyanide method). The result of analysis in phenolic content showed that pith extract at immersion time of first day higher compared with second and third days. The result is in line with free radical scavenging measuring with immersion time of first day higher than second and third days. Likewise, the total antioxidant, antioxidant capacity and reducing power also showed that pith extract in immersion time of first day has highest antioxidant capacity than second and third days. There is effect that immersion time of sago baruk pith influence on phenolic content and antioxidant activity. This result concluded that sago baruk pith extract having phenolic compound and antioxidant activities. There is effect that immersion time of sago baruk pith influence on phenolic content and antioxidant activity. This result concluded that sago baruk pith extract having phenolic compound and antioxidant activities.